Absence of cross-reactivity to myeloperoxidase of anti-thyroid microsomal antibodies in patients with autoimmune thyroid diseases - Freire, B. A.; Paula, I. D.; Paula, F.; Kallenberg, GGM; Limburg, P. C.; Queluz, Thais Helena Abrahão Thomaz [UNESP] (Lippincott Williams & Wilkins, 2001)
Background: Thyroperoxidase is the major antigen of the thyroid microsomal antibodies (TMA) detected in autoimmune thyroid diseases. Its amino acid sequence has 44% homology with myeloperoxidase (MPO), an enzyme present in the primary granules of neutrophils and one of the major antineutrophil cytoplasmic antibodies (ANCA) antigens. The objective of the present study was to investigate the presence of cross-reactivity to MPO of TMA. Methods: We studied sera from 51 patients with autoimmune thyroid diseases, all of them TMA-positive. The presence of ANCA was investigated by indirect immunofluorescence and by capture enzyme-linked immunosorbent assay. Results: ANCA were positive in 3.9% of the TMA-positive sera and none of them reacted with MPO. In contrast, the ANCA-positive sera revealed antielastase activity. None of the ANCA-positive cases presented clinical signs of vasculitis. However, these 2 patients had been on prolonged treatment with propylthiouracil. Conclusions: We conclude that there is no cross-reactivity to MPO of TMA in patients with autoimmune thyroid diseases, possibly because of difference in the spatial configuration of the immunodominant region. The presence of ANCA in patients with autoimmune thyroid diseases without evidence of vasculitis might result from propylthiouracil-induced polyclonal activation.
Keywords: antineutrophil cytoplasmic antibodies; anti-thyroid peroxidase antibodies; autoimmune thyroid disease; cross-reactivity; myeloperoxidase